Jawabanmu

2014-04-26T20:09:28+07:00
p.k 2x² - 4x + 5 = 0.
a) PKB  2(x-2)² - 4(x-2) +5 = 0 ⇔ 2(x² - 4x + 4) - 4x + 8 + 5 =0
                                             ⇔ 2x² - 8x + 8 - 4x + 13 = 0
                                             ⇔ 2x² - 12x + 21 = 0

b) x1² + x2² = (x1 + x2)² - 2x1x2
                  = (-b/a)² - 2c/a
                  = (4/2)² - 10/2
                  = 4 - 5
                  = - 1
   x1²x2² = (x1x2)²
             = (5/2)²
             = 25/4
  PKB : x² - (x1² + x2²)x + x1²x2² = 0
            x² - (-1)x + 25/4 = 0   

            x²  + x + 25/4 = 0 atau 4x² + 4x + 25 = 0

c)  x1/x2 + x2/x1 = x1² + x2²
                               x1x2
                          = -1/(25/4)
                          = - 4/25
     x1/x2.x2/x1  = x1x2 = 1
                           x2x1
     PKB x² - (x1/x2 + x2/x)x - x1/x2.x2/x1 = 0
             x² - (-4/5)x - 1 = 0
             x² + 4x/5  - 1  atau  5x² + 4x - 5 = 0